Optimasi Pemanfaatan Sumber Air Untuk Irigasi Berkelanjutan Menggunakan Metode F.J. Mock dan CROPWAT 8.0. - Sulwan Permana; Muhammad Diki Paris (Institut Teknologi Garut, 2026)
The Indralayang area, Garut Regency, has high agricultural potential but often faces challenges in managing water resources due to fluctuations in availability and irrigation demand. This study aims to analyze water resource availability, irrigation water requirements, and determine the most efficient irrigation techniques to support sustainable agriculture systems. The analysis was conducted using the F.J. Mock water balance method to estimate water availability and CROPWAT 8.0 simulations to calculate evapotranspiration, effective rainfall, and crop water requirements.The results show that irrigation water demand amounts to 27,090.83 liters/second, while water availability reaches 29,477.35 liters/second. This indicates a water surplus of 2,386.52 liters/second, with a demand-to-availability ratio of approximately 91.9%, meaning that water resources are sufficient to meet the irrigation needs of 696 hectares of farmland. Given the relatively abundant water supply, the most appropriate irrigation technique is surface irrigation (gravity surface irrigation), complemented by land leveling, channel improvements to reduce water loss, and the application of the Alternate Wetting and Drying (AWD) method in rice fields to enhance water use efficiency.This study contributes to the planning of sustainable irrigation systems in lowland agricultural areas.